Os Estágios Curriculares Supervisionados nos cursos de Licenciatura em Educação Física do Rio Grande do Sul: impacto das 400 horas. - Montiel, Fabiana Celente (2010)
An important curriculum component for the initial formation is the Curricular Supervised Training (CST), which can be considered the first contact with professional reality. In 2002 the National Education Council - Full Council (NEC/FC) by Resolution n. 2 established the duration and hours of teaching, full graduation, of teacher training education at higher level, having the courses to adapt themselves this resolution until 15 October 2005. From the changes resulting from resolution of the hours of teaching go from 300 to 400 hours. News and changes in pedagogical situations do not always occur as expected and changes generally have an early impact in its actual implementation may cause unwanted situations, and seeks to analyze the changes in teaching degree in Physical Education (PE) of the RS, and their impact, from the current curriculum changes in legislation in relation to CST. The study covered the Degree courses in the EF of RS, headquarters courses, with 17 Universities of Physical Education (UPE), created until 2000 which in the past had the CST with 300 hours. It was used as research tool questionnaires, which were sent to the course coordinators of the UPE and the faculty advisers of CST, a professor from each UPE. It was also asked to review the Project of the Course (PC) of the UPE studied in order to verify, through an analysis of documents, the existence of minimum hours of 400 hours for CST, the location and distribution of CST in the curriculum, the existence of prerequisites for the achievement of this training and harmonization among the subjects taken. It was noted that the major impacts perceived by course coordinators and university advisors are related to the large number of students in schools, making it difficult for the trainees to care for students in CST, apart from that there is a need for greater partnership between school and university, where everyone works together for the training of the future teachers of PE. Regarding the location of the CST they according to the new legislation, from the second half of the course on, thus facilitating the relationship between theory and practice, no longer a single step at the end of the course. Even half of the UPE not showing more prerequisites for the implementation of CST, they suggest a pedagogical in order to make the student ready to enter the school. We believe that the changes imply processes which demand some time for its conclusion although from the changes established by Resolution NEC/FC 01/2002 and Resolution NEC/FC 02/2002, have perceived positive changes in the structuring of courses of Degree in PE, as showing the ideas, which case could be the interaction between theory and practice in training courses for teachers of PE in RS.